Postwar: Art Between the Pacific and the Atlantic. 1945-1965. - Enwezor, Okwui; Anreus, Alejandro; Azoulay, Ariella; Bahrani, Zaineb; Bhabha, Homi K.; Braun, Emily; Degot, Ekaterina; Denegri, Jesa; Drosos, Nikolos; Erber, Pedro; Minglu, Gao; Golan, Romy; et al. (München : Prestel Verlag, 2016)
Abboud, Shafic ; Affandi ; Akyavas, Erol ; Al-Moudarres, Fateh ; Andre, Carl ; Appel, Karel ; Araeen, Rasheed ; Acay, Wilfredo ; Armajani, Siah ; Baj, Enrico ; Bearden, Romare ; Berman, Mieczyslaw ; Berni, Antonio ; Beys, Joseph ; Biggers, John ; Bill, Max ; Bontecou, les ; Boshier, derek ; Boudnik, Vladimir ; Bowling, Frank ; Burri, Alberto ; Chandra, Avinash ; Cherakaoui, Ahmed ; Raouda Choucair, Saloua ; Clark, Lygia ; Conner, Bruce ; Cordeiro, Waldemar ; Cordell, Magda ; Darié, Sandu ; delaney, Beauford ; Divis, alen ; Edwards, Melvin ; Efflatoun, Inji ; Egonu, Uzo ; El Salahi, Ibrahim ; Emokpae, Erhabor ; Enwonwu, Ben ; Fahlstrom, Öyvind ; Fangor, Wojiech ; Fattah, ismail ; Frankenthaler, Helen ; Gattin, Ivo ; Golub, leon ; Herrera, Carmen ; Hesse, Eva ; Lawrence, Jacob ; Ufan, Lee ; Mancabo, Ernest ; Neel, Alice ; Mitchell, Joan ; Pape, Lygia ; Selim, Jewad ; Schneemann, Carolee ; Shiraga, Kazuo ; Sirri, Gazbia ; Atsuko, Tanaka ; Stella, Frank ; Tobey, Mark ; Whitten, Jack ; Vedova, Emilio ; Younan, Ramses ; Zlotnikov, Yuri
Global South, dekolonisatie
Postwar: Art Between the Pacific and the Atlantic, 1945-1965, Haus der Kunst, Munchen, van 14 oktober 2016 tot 26 maart 2017
boek